1992
DOI: 10.1002/ccd.1810250306
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of anticoagulation and radiographic contrast agents to thrombosis during coronary angiography and angioplasty: Are there real concerns?

Abstract: Radiographic contrast agents are essential for the performance of coronary angiography and angioplasty. Historical data show that thrombosis-related events have occurred since coronary angiography has been performed. Newer non-ionic agents have been shown to be safer than conventional high osmolar ionic agents especially in high risk patients, but concern has been raised about a potentially increased risk of thrombosis with the use of these agents. A review of basic and clinical evidence for this perception do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…Although some studies 4,8 described the risk for thrombosis, we did not observe this effect of contrast material on platelet function. Before injection, PF-3 availability was prolonged, but decreased somewhat after iopamidol was infused, although all values remained within the normal range.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Although some studies 4,8 described the risk for thrombosis, we did not observe this effect of contrast material on platelet function. Before injection, PF-3 availability was prolonged, but decreased somewhat after iopamidol was infused, although all values remained within the normal range.…”
Section: Discussioncontrasting
confidence: 97%
“…Ionic contrast material prolongs anticoagulation by inhibiting platelet activation. 4 Stormorken et al 17 and Dawson et al 18 demonstrated that both ionic and nonionic materials prolong aPTT and thrombin time. Grabowski 19 showed that iopamidol prolongs clotting time in whole blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A contemporary study based on 1,609 diagnostic catheterizations performed in 1986 and 1987 reported that the incidence of death was 0.12%, the rate of embolic events was 0.2%, and that there were no myocardial infarctions [ 131. A more recent review reports that the current incidence of embolic or thrombotic complications is even further reduced [14]. It is uncertain from these reports whether complications such as death and myocardial infarction were definitely related to thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the radial routes are known to have increased radiation dosage to patients and the physicians [12], [13]. Contrast agents are also associated with thrombotic and bleeding manifestations, which was observed in various studies [14], [15], [16], [17], [18]. They are well known to induce platelet degranulation [19].…”
Section: Introductionmentioning
confidence: 99%